2005
DOI: 10.1094/phyto-95-0381
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Transcripts Involved in Resistance Responses to Leaf Spot Disease Caused by Cercosporidium personatum in Peanut (Arachis hypogaea)

Abstract: Late leaf spot disease caused by Cercosporidium personatum is one of the most destructive foliar diseases of peanut (Arachis hypogaea) worldwide. The objective of this research was to identify resistance genes in response to leaf spot disease using microarray and real-time polymerase chain reaction (PCR). To identify transcripts involved in disease resistance, we studied the gene expression profiles in two peanut genotypes, resistant or susceptible to leaf spot disease, using cDNA microarray containing 384 uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 42 publications
0
52
0
Order By: Relevance
“…qRT-PCR assays were performed in a F7300 Real Time PCR (Applied Biosystems, Foster City, CA, USA) using 5 mL Platinum SYBR Green qPCR Super Mix-UDG w/ROX kit (Invitrogen) in a 10-mL final volume reaction containing 2 mL diluted cDNA and 0.2 mM of each primer. The following two reference genes were used: Arachis Ubiquitin (Fwd-5'AAGCCGAAGAAGATCAAGCAC3', Rev-5'GGTTAGCCATGAAGGTTCCAG3') (Luo et al, 2005) and Ribosomal 60S (Fwd-5'GAGCTGAAAGATTCCGATGC3', Rev-5'GCAATGCCTGGGAACATAGTC3') (Jain et al, 2006). Those two pairs for primers were designed in intron flanking regions which also allows the distinction between PCR products amplified from genomic DNA and cDNA templates.…”
Section: Relative Expression Of Rs Genesmentioning
confidence: 99%
“…qRT-PCR assays were performed in a F7300 Real Time PCR (Applied Biosystems, Foster City, CA, USA) using 5 mL Platinum SYBR Green qPCR Super Mix-UDG w/ROX kit (Invitrogen) in a 10-mL final volume reaction containing 2 mL diluted cDNA and 0.2 mM of each primer. The following two reference genes were used: Arachis Ubiquitin (Fwd-5'AAGCCGAAGAAGATCAAGCAC3', Rev-5'GGTTAGCCATGAAGGTTCCAG3') (Luo et al, 2005) and Ribosomal 60S (Fwd-5'GAGCTGAAAGATTCCGATGC3', Rev-5'GCAATGCCTGGGAACATAGTC3') (Jain et al, 2006). Those two pairs for primers were designed in intron flanking regions which also allows the distinction between PCR products amplified from genomic DNA and cDNA templates.…”
Section: Relative Expression Of Rs Genesmentioning
confidence: 99%
“…Near isogenic lines (NILs) developed for rust resistance were thoroughly screened with both foreground and background molecular markers (Yeri et al, 2014). For the identification of LLS resistance, Luo et al (2005b) identified genes in the resistant genotype that were more highly expressed than in the susceptible genotype (in response to Cercosporidium personatum infection) by microarray analysis and validated them by real-time PCR. In a recombinant inbred line (RIL) population (VG 9514 Â TAG 24), two transposable element (TE) markers, TE 360 and TE 498, were found to be associated with the rust resistance gene.…”
Section: Markers Associated With Rust and Lls Resistance Gene(s)mentioning
confidence: 99%
“…Macroarray (nylonbased) and microarray (glass slide-based) screening methods allow the simultaneous determination of expression levels of thousands of genes, making it possible to obtain a global view of the transcriptional state in a cell or tissue, and to associate genes with functions or specific physiological conditions. Recently, microarray technology has been demonstrated in a small scale pilot studies (Luo et al, 2005b;Luo et al, 2005c). EST-derived cDNA microarrays of 400 unigenes were probed under different conditions.…”
Section: Functional Genomics and Control Strategies Of Aflatoxin Contmentioning
confidence: 99%